Obtenção de farinha de banana verde para produção de cookie - Candeo, Naiara Nair Rosa (2019)
Brazil is responsible for the largest production of banana in the world, and banana’s high availability makes it possible to use as an option to enrich food products. In this work the banana was used in a green stage, and it was submitted to a drying technique, to obtain flour for later production of different cookie type. The objective of the present work was to obtain green banana flour for the production of a cookie and to characterize the physical and chemical aspects of both flour and cookie. After the production of both, the moisture, ash and protein contents were analyzed and compared to a standard cookie produced with wheat flour. The results were satisfactory in relation to the studied aspects when compared to the standard cookie, since all the determinations were presented according to legislation. A visual analysis of the final product produced from green banana flour was found to be similar to other commercialized cookies. Therefore, the work concluded that the production of green banana flour it’s an option in the substitution of wheat flour for application in food products resulting in a functional food.